Enhancing maritime english through intercultural communication strategies: lessons from indonesian and korean seafarers - Tristanti Tristanti; Jin-Chul Choi; Fauzan Atsari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Effective communication is vital for ensuring safety, efficiency, and teamwork in multicultural maritime environments. However, cultural differences often create communication barriers that extend beyond language. This study aims to identify intercultural communication barriers between Indonesian and South Korean seafarers and to propose English learning strategies for seafarers, based on intercultural communication principles, to enhance linguistic competence and cultural awareness. Using a qualitative descriptive design, data were collected through in-depth interviews and participant observations involving eight Indonesian seafarers who had worked with Korean crews. Thematic analysis with NVivo 12 identified recurring patterns of communication barriers and adaptive strategies. Findings revealed five dominant barriers: language, hierarchy, communication style, work ethics, and cultural sensitivity. To address these challenges, six pedagogical strategies for Maritime English instruction are proposed, including Task-Based Language Learning, simulation and role-play, collaborative and reflective learning, technology integration, and intercultural awareness modules. This study contributes to the development of Maritime English education by embedding intercultural communication principles into English learning for seafarers, preparing them to communicate more effectively, respectfully, and professionally in diverse global maritime workplaces. By understanding these barriers, practical solutions and improved strategies can foster more effective intercultural interaction among seafarers from these two distinct cultural backgrounds.